Co-, N-doped carbon dot nanozymes based on an untriggered ROS generation approach for anti-biofilm activities and in vivo anti-bacterial treatment - Dong, Wenpei; Xu, Lingyun; Chen, Mengting; Jiang, Tao; Su, Li; Ma, Jinliang; Chen, Chang-po; Zhang, Guisheng (Journal of materials chemistry. B, Materials for biology and medicine, 2024)
Bacterial infections originating from food, water, and soil are widely recognized as significant global public health concerns. Biofilms are implicated in approximately two-thirds of bacterial infections. In recent times, nanomaterials have emerged as potential agents for combating biofilms and bacteria, with many of them being activated by light and H 2 O 2 to generate reactive oxygen species (ROS). However, this energy-consuming and extrinsic substrate pattern poses many challenges for practical application. Consequently, there is a pressing need to develop methods for the untriggered generation of ROS to effectively address biofilm and bacterial infections. In this study, we investigated the oxidase-like activity of the Co,N-doped carbon dot (CoNCD) nanozyme, which facilitated the oxidation of ambient O 2 to generate 1 O 2 in the absence of light and H 2 O 2 supplementation; this resulted in effective biofilm cleavage and enhanced bactericidal effects. CoNCDs could become a potential candidate for wound healing and treatment of acute peritonitis in vivo , which can be primarily attributed to the spontaneous production of ROS. This study presents a convenient ROS generator that does not necessitate any specific triggering conditions. The nanozyme properties of CoNCDs exhibit significant promise as a potential remedy for diseases, specifically as an anti-biofilm and anti-bacterial agent.